Speckle Theory for Arbitrary Wavefront Illumination in Free-Space Surface Scattering - Qiyong Xu; Janan Zhou; Yipeng Mo; Zichun Le (IEEE Photonics Journal)
Speckle has been shown to cause significant degradation to the imaging quality of laser imaging systems. However, in certain complex imaging environments, it can also act as an effective information carrier. Therefore, accurate characterization of speckle is imperative. In this study, a speckle characterization theoretical model, which describes the features of speckle at arbitrary wavefront illumination in a free-space surface scattering optical path, is developed and experimentally verified. The current study elucidates the combined effect of illumination wavefront and laser wavelength on speckle contrast, further refining the statistical theory of speckle. The findings have potential applications in the prediction of speckle characteristics or environmental parameters, and are primarily relevant to non-imaging optics-related fields.